Effect of oxalic acid on Nosema ceranae infection. (October 2015) - Nanetti, Antonio; Rodriguez-García, Cristina; Meana, Aránzazu; Martín-Hernández, Raquel; Higes, Mariano
Abstract: Nosema ceranae is a honey bee pathogen parasitizing the ventricular epithelium and potentially causing colony death. The effect of 0.25 M oxalic acid solution administered to the bees in the form of sugar syrup was determined in laboratory and field trials. The spore numbers in an 8-day laboratory experiment were significantly lower when AO was administered (treated: 11.86 ± 0.94 s.e. × 10^6; untreated: 30.64 ± 0.31 s.e. x 10^6). When administered in autumn to free flying colonies twice, 3 weeks apart, the infection prevalence decreased in young (relative reduction of 53.8% ± 6.5 s.e.) and old bees (relative reduction of 44.4% ± 6.0 s.e.). Meanwhile increased prevalence in all the controls was detected (young and old bees: relative increase of 45.7% ± 22.8 s.e. and 10.2% ± 5.9 s.e., respectively). While all the treated colonies overwintered correctly, the untreated ones did not (3 out of 5 were dead). In the absence of commercial products approved in several countries to control nosemosis, oxalic acid syrup appears promising in the development of alternative management strategies. Highlights: We tested whether oxalic acid controls the honey bee parasite Nosema ceranae . In the laboratory, oral applications hindered the increase rate of artificial infections. In the field, two topical administrations decreased prevalence in young and old bees. Increased prevalence and overwintering failure were observed in untreated colonies. We conclude that oxalic acid can be used to control N. ceranae infections.